A review on multi-therapeutic potential of the Mitragyna speciosa (kratom) alkaloids mitragynine and 7-hydroxymitragynine: experimental evidence and future perspectives - Begum, Taslima; Arzmi, Mohd Hafiz; Sarian, Murni Nazira; Ali Shah, Syed Adnan; Azmi, Syed Najmul Hejaz; Helal Uddin, A.B.M.; Khatib, Alfi; Ahmed, Qamar Uddin (Elsevier B.V., 2025)
Mitragyna speciosa (kratom) is a traditional medicinal plant of Southeast Asia, known for its pharmacologically active alkaloids, Mitragynine and 7-hydroxymitragynine. The chemistry, isolation, pharmacological properties, and toxicities of these two compounds have been studied by a wide range of scientific studies. However, thus far, there is no comprehensive review of Mitragynine, 7-hydroxymitragynine, and their related compounds. Therefore, this review analyzed 150 papers from PubMed®, ScienceDirect, and Google Scholar to provide information on the chemistry, method of synthesis and extraction, biological effects, and toxicities of Mitragynine and 7- hydroxymitragynine. Additionally, the existing research gaps were identified and recommendations for future research were provided. It was observed that most studies focused on Mitragyna speciosa leaves, with little to no research conducted on other parts of the plant, particularly the flowers. Furthermore, there is still a lack of less costly and time-consuming protocols to obtain the two major alkaloids from different parts of the plant. Finally, most studies have focused on these two alkaloids to explore their pharmacological effects, although some studies have shown that other alkaloids exhibit better pharmacological activity.